Influence of the indirect restoration design on the fracture resistance: a finite element study. Issue 1 (December 2016) - Mei, May; Chen, Ya; Li, Hao; Chu, Chun
Abstract Objectives To establish a three-dimensional (3D) finite element (FE) model of a maxillary first premolar and to evaluate the stress generated on the tooth (dentine) and on the indirect composite resin restorations by occlusal forces. Methods An embedded intact maxillary first premolar tooth was sliced serially and scanned digitally parallel to the occlusal surface. The 64 images were assembled in a 3D FE mesh and exported to generate a 3D solid tooth model. Simulated, adhesively cemented indirect mesial-occlusal-distal (MOD) inlays of 2 mm (I1), 3 mm (I2) and 4 mm (I3) in width, and MOD onlays with occlusal cusp coverage of 2 mm (O1) and 3 mm (O2) in depth were created. The peak von Mises stress values in the five tooth models resulting from static vertical and oblique occlusal forces (300 N) were evaluated using Patran FE software. Results The peak stress values generated by vertical occlusal force generated in dentine of I1, I2, I3, O1 and O2 restoration were 67, 32, 29, 38 and 27 MPa, respectively, and those generated by oblique occlusal force were 52, 114, 168, 54 and 55 MPa, respectively. The peak von Mises stress values in I1, I2, I3, O1 and O2 restoration subjected to oblique occlusal loading were 79, 120, 1740, 1400 and 1170 MPa, respectively. Conclusion A 3D FE model of a maxillary first premolar was established. Simulated cemented composite resin onlay markedly reduces occlusal stress in the underlying dentine of large MOD preparation. Oblique occlusal force imparts substantially higher stress to large composite resin inlay than to the adjacent dentine.